2021
DOI: 10.1186/s13223-021-00635-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing telemedicine use in clinical immunology and allergy in Canada before the COVID-19 pandemic

Abstract: Rationale There exists a geographic barrier to access CIA care for patients who live in rural communities; telemedicine may bridge this gap in care. Herein we characterized the use of telemedicine in CIA at a population-based level and single centre. Methods Before the COVID-19 pandemic, telemedicine care was provided via the Ontario Telemedicine Network (OTN) in Ontario, Canada. Descriptive data were collected from the OTN administrative database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…This is of particular interest in a time of transition between virtual and in-person care, increased waittimes for specialist consultation, and the known psychological impact this may have on patients (21). As with many other specialties, the general uptake of telemedicine in the eld of CIA was relatively low prior to the COVID-19 pandemic (22), however, emerging data has clearly demonstrated that CIA can effectively and safely implement such a system (5,6). This is of signi cance, as the Canadian Medical Association has only 219 allergists registered as of 2019, with no practicing allergist available in Prince Edward Island, New Brunswick, or the Territories (23).…”
Section: Resultsmentioning
confidence: 99%
“…This is of particular interest in a time of transition between virtual and in-person care, increased waittimes for specialist consultation, and the known psychological impact this may have on patients (21). As with many other specialties, the general uptake of telemedicine in the eld of CIA was relatively low prior to the COVID-19 pandemic (22), however, emerging data has clearly demonstrated that CIA can effectively and safely implement such a system (5,6). This is of signi cance, as the Canadian Medical Association has only 219 allergists registered as of 2019, with no practicing allergist available in Prince Edward Island, New Brunswick, or the Territories (23).…”
Section: Resultsmentioning
confidence: 99%
“…The role of immune exhaustion and immune suppression in severe COVID-19 outcomes is becoming more firmly established. Lee et al found that a low CD4 þ /CD8 þ ratio was highly predictive of poor outcomes in COVID-19 and other infectious diseases in the general population [13]. Data from the Center for AIDS Research Network of Integrated Clinical Systems (CNICS) cohort demonstrate that low CD4 þ /CD8 þ ratio and low nadir CD4 þ T-cell count are associated with COVID-19 incidence [26], and older age, no ART, and low CD4 þ T-cell count are associated with intubation and mortality in PWH [12].…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Limitations include retrospective study design, which did not allow for control of all possible confounders. Our study was cross-sectional, and included demographic, clinical, and laboratory data at the time of COVID-19 diagnosis, but we were unable to account for longitudinal variables that may be relevant, including duration of comorbidities, duration of HIV infection, CD4 þ T-cell nadir, or ART history, particularly as CD4 þ T-cell nadir and other markers of immune dysfunction have been associated with poor COVID-19 outcomes [12,13]. Our cohort had an overrepresentation of PWH who were virally suppressed on ART compared with the local HIV epidemic [37], likely a result of persons already engaged in medical care seeking COVID-19 testing and treatment.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, access to specialist care in Canada has been limited by their shortage as well as the distance between patients and their physicians. A recent paper published by Lee et al advocated for the use of telemedicine to bridge Allergy and Immunology care to patients with limited access in remote communities [ 13 ].…”
Section: Introductionmentioning
confidence: 99%